A Study on the Development of Reading Skills of the Students Having Difficulty in Reading: Enrichment Reading Program - Hayati AKYOL; Ahmet ÇAKIROĞLU; Hayriye Gül KURUYER (International Electronic Journal of Elementary Education, 2014)
The aim of this study is to improve the reading skills of the students having difficulty in reading through an enrichment reading program. The current study was conducted by means of one-subject research technique and between-subjects multiple-starting levels model belonging to this technique. The study was carried out with three participants from fifth grade. In order to collect data for the study, word recognition test, reading texts, Ekwall and Shanker reading inventory and reading comprehension test were employed. In line with the purposes of the study, the collected data were analyzed through qualitative and quantitative tests and the results were explained as qualitative and quantitative. At the end of the study, it was found that some developments occurred on the participants’ word recognition skills and aloud reading skills. It was concluded that for the development of the reading skills of the students having reading difficulty, construction of appropriate reading environment and implementation of enrichment reading programs can be effective.